2019
DOI: 10.1111/zph.12568
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to human rabies elimination highlighted following a rabies outbreak in bovines and a human in Punjab, India

Abstract: In August 2015, a rabies outbreak occurred in bovines in a Punjab village, India; subsequently, a farmer in the same village died of rabies in October 2015. We surveyed farmers to describe the outbreak, the demographics and rabies prophylaxis administered to householders on case farms, and farmers’ knowledge of rabies prevention and treatment. We used multiple correspondence analysis to guide investigation of associations between demographics, farm status and rabies knowledge, attitudes and practices. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Studies in India found some participants had heard about rabies, but knowledge of first-aid following a bite was poor, with application of chillies, turmeric or kerosene and visiting traditional healers recommended [ 33 , 35 , 37 ]. In two Pakistan studies, most participants stated there had been no rabies awareness campaign in their community [ 28 , 38 ], with similar findings in India [ 32 , 35 ]. People reported getting their information from friends, family and neighbours, with women who had received no formal education likely to be less aware of the disease [ 32 ].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Studies in India found some participants had heard about rabies, but knowledge of first-aid following a bite was poor, with application of chillies, turmeric or kerosene and visiting traditional healers recommended [ 33 , 35 , 37 ]. In two Pakistan studies, most participants stated there had been no rabies awareness campaign in their community [ 28 , 38 ], with similar findings in India [ 32 , 35 ]. People reported getting their information from friends, family and neighbours, with women who had received no formal education likely to be less aware of the disease [ 32 ].…”
Section: Resultsmentioning
confidence: 85%
“…In two Pakistan studies, most participants stated there had been no rabies awareness campaign in their community [ 28 , 38 ], with similar findings in India [ 32 , 35 ]. People reported getting their information from friends, family and neighbours, with women who had received no formal education likely to be less aware of the disease [ 32 ]. Other common sources of information included media and television [ 30 , 37 ].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Both stray cattle and stray dogs are mostly dependent on food sources associated with the human population and therefore, are likely to have an overlapping home range. Cattle or buffaloes have previously been reported to be more likely to be bitten when kept in streets and open ground areas in Punjab [26]. However, we are not aware of any scientific investigation conducted to investigate stray cattle and dog home ranges and further investigations are required to fully elucidate this association.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors highlighted additional emerging zoonotic viral pathogens in the food animal workforce, including a report of brucellosis among sheep farmers in Egypt and knowledge and biosecurity practices among Indian animal farmers about rabies [46,47]. Msimang and colleagues reported on Rift Valley fever seroprevalence among animal farmers and veterinarians in South Africa, concluding that infection with this re-emerging pathogen is likely notably higher than previously recognized and under-diagnosed in the region [50].…”
Section: Other Viral Infectionsmentioning
confidence: 99%